An Exploratory Study on the Environmental Behavior of Agro-Businesses in Selangor - Kinikachi, Owhonda (2012)
Environment sustainability is one of the major problems of the new millennium. Continuous degradation of the environment is causing severe problems such as climate change, water supply shortage and loss of biodiversity. Saving the environment is thus an urgent necessity and requires a strategic understanding on environment behavior of all stakeholders of an economy, especially the business sectors as they are regarded as primary contributor to environmental problems. One of the key approaches in understanding environmental behavior is to understand waste management practices of business sector. Disposing waste is part and parcel in a business operation. However less attention is given to understand how businesses manage waste disposal by considering the impact to the environment. This research explored the environmental behavior of agriculture based business in the state of Selangor, Malaysia. The agriculture sector was chosen because it represents one of the key players of Malaysia’s economic growth, via production of agrobased products and its exports. Using the case study research approach, in depth interviews with five sample agriculture based businesses (with 5 interviewees in each firm) were undertaken to understand current waste management practices, the cost and benefits of environmental friendly waste management practices, the cost and benefits of environmental friendly waste management, the motivations to undertake environmental friendly waste management, the awareness and knowledge toward environmental friendly waste management, and the extent government support is perceived to drive environmental friendly waste management in this business sector. Thematic analysis on the data collected from the 25 respondents of the five companies’ revealed formation of several themes which are summarized as follows. Firstly, in the context of current waste management practice, majority of the respondents are not practicing environmental friendly based waste management as required by local and federal regulations. Second, in terms of the cost and benefits issue, the result showcase that the cost of undertaking environmental friendly waste management is higher than the expected benefits which links largely on return on investment issue. Thirdly, most respondents are not motivated to undertake environmental friendly based waste management. Fourth, the level of awareness and knowledge toward environmental friendly waste management amongst the respondents are pervasive but not practiced. Lastly, majority of the respondents are in the view that at macro level, government provides adequate support to undertake environmental friendly waste management. However issues and restriction emerge when it comes to operationalization of waste management – mostly from lower level governmental departments. This presumably hinders effective environmental friendly waste management. The outcome of this research has theoretical and practical implications and has been discussed in Chapter 5. Further recommendations and suggestions are also given in Chapter 5.